Avaliando a experiência do usuário de longo prazo em aplicações m-Health - Biduski, Daiana (2019)
The widespread adoption of smartphones provides new opportunities for improving health care through mobile health applications, known as mHealth. Although these applications have many features, their acceptance rates are still modest. In this context, providing a satisfying experience is critical for the user to feel motivated over time. Long-term UX refers to the experience over a given period of use. In long-term evaluations, practicality is a key factor for participants' attendance and commitment. Thus, longer periods of use may reveal the possible impact of a set of experiences. In this study, the objective was to investigate the long-term user experience in m-Health applications to identify how it occurs over time, using an online questionnaire available through a conversational interface. The study was developed in nine stages: characterization of the problem, search for UX factors, elaboration and validation of the questionnaire, experimentation period with questionnaire applied before, during and after use, conversation with users and information mapping. Data from three different mHealth applications were collected to not restrict the concept to a single health condition, divided into three groups of users. For 12 weeks, users reported their experiences with the application, describing their impressions regarding usage. In general, the use of the application for health monitoring was considered positive. The results demonstrated the most satisfactory experiences were associated mainly within the first weeks of the study, which focused on functionalities, visual resources and the practicality of monitoring with the use of an application. For the less satisfactory experiences, the main reasons identified were the difficulty of use, technical problems in the application and the effort required to use. About this, figures are presented summarizing information about the health and experience of each user before, during and after use. The tables represent the study’s sample, responses on the characterization of the problem and the questions included in the evaluation questionnaire. Less experienced users, either using other monitoring methods or not monitoring their health at all, proved to be more resistant while interacting with the application. Features praised by the users in the first few weeks of use were later criticized for technical and usability issues that users had not identified during the first few weeks. The use of character in the conversational interface as mediator of the assessment questionnaire was appreciated by all users. Further research must expand the scope of m-Health applications, including the use of appropriate assessment methods to validate the obtained results.